2011
DOI: 10.1105/tpc.110.076018
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Hsp90 and Hsp70 Chaperones and Heat Stress Transcription Factors in Tomato

Abstract: Heat stress transcription factors (Hsfs) regulate gene expression in response to environmental stress. The Hsf network in plants is controlled at the transcriptional level by cooperation of distinct Hsf members and by interaction with chaperones. We found two general mechanisms of Hsf regulation by chaperones while analyzing the three major Hsfs, A1, A2, and B1, in tomato (Solanum lycopersicum). First, Hsp70 and Hsp90 regulate Hsf function by direct interactions. Hsp70 represses the activity of HsfA1, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
264
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 299 publications
(294 citation statements)
references
References 68 publications
16
264
0
Order By: Relevance
“…Hsp27 in mammalian cells has been shown to be present in the nucleus where it interacts with the transcription factor SP1 and stimulates SP1-mediated gene expression (Friedman et al 2009). More recently, Hsp70 and Hsp90 have been shown to regulate the activities of HsfA1, HsfA2, and HsfB1 in tomato (Hahn et al 2011). Notably, OsClpB-cyt is localized in cytoplasm while OsHsfA2c:OsClpB-cyt complex is localized in nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Hsp27 in mammalian cells has been shown to be present in the nucleus where it interacts with the transcription factor SP1 and stimulates SP1-mediated gene expression (Friedman et al 2009). More recently, Hsp70 and Hsp90 have been shown to regulate the activities of HsfA1, HsfA2, and HsfB1 in tomato (Hahn et al 2011). Notably, OsClpB-cyt is localized in cytoplasm while OsHsfA2c:OsClpB-cyt complex is localized in nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Heat stress transcription factors (Hsfs) and heat shock proteins (Hsps) are central in conferring heat tolerance (Saidi et al, 2011;Hahn et al, 2011). Previous studies in tomato have identified three Hsf genes (HsfA1, HsfA2, and HsfB1) and four Hsp genes (Hsp100, Hsp90, Hsp70, and HspII17.6) that play important roles in heat stress response (Mishra et al, 2002;ChanSchaminet et al, 2009;Giorno et al, 2010;Hahn et al, 2011;Li et al, 2012).…”
Section: Cwin-elevated Transgenic Tomato Exhibited a Sustained Or Incmentioning
confidence: 99%
“…In tomato, the fundamental Hsf network for control of HSR depends on the activities of HsfA1a, HsfA2, and HsfB1 (Hahn et al, 2011). HsfA1a and HsfB1 are constitutively expressed with mRNA steady state levels of low abundance.…”
mentioning
confidence: 99%
“…The transcripts of HsfA2 are hardly detectable under control temperature conditions, but upon HS, the accumulation of HsfA2 mRNA and protein is strongly induced. Consequently, HsfA2 becomes the most abundant Hsf during recovery or after several cycles of repeated HS (Hahn et al, 2011;Scharf et al, 1998). During recovery from HS, the availability of HsfA2 is controlled at the protein level by interactions with class CI and CII small Hsps (sHsps) and the activity of higher molecular weight chaperones such as Hsp70 and Hsp101 (Port et al, 2004).…”
mentioning
confidence: 99%